2007
DOI: 10.1007/s00277-007-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma-associated hemophagocytic syndrome: clinical features and treatment outcome

Abstract: The clinical features and prognostic factor of lymphoma-associated hemophagocytic syndrome (LAHS), diagnosed according to World Health Organization classification, were investigated by reviewing the clinical records of 29 patients between September 1994 and September 2006. Compared with patients with T or natural killer (NK)/T cell LAHS, patients with B cell LAHS were older (p = 0.022), were less likely to exhibit disseminated intravascular coagulation (DIC; p = 0.011), and had less direct involvement of bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 19 publications
10
109
2
3
Order By: Relevance
“…Machaczka [15] examined eight patients and found that only one patient with HLH-04 who was treated with an allogeneic stem cell transplant survived. In another article by Tong [2], long-term survival was achieved in four out of 29 patients, three of which received autologous stem cell transplants. The present HLH patient relapsed during the fourth week of treatment after decreasing the etoposide and immunosuppressive regimen, which suggested that regimen like HLH-04 alone is not sufficient to control lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machaczka [15] examined eight patients and found that only one patient with HLH-04 who was treated with an allogeneic stem cell transplant survived. In another article by Tong [2], long-term survival was achieved in four out of 29 patients, three of which received autologous stem cell transplants. The present HLH patient relapsed during the fourth week of treatment after decreasing the etoposide and immunosuppressive regimen, which suggested that regimen like HLH-04 alone is not sufficient to control lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of HLH secondary to lymphoma is unfavorable, and the median survival time is less than 40 days [2,10]. Importantly, survival has been shown to be dependent on the type of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] The central pathogenesis involves dysregulated Th1 cytokine secretion. This results in an uncontrolled accumulation of activated T-lymphocytes and histiocytes in various organs including the liver, spleen and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…6 Viruses are the most common infectious triggers of HLH, particularly EBV, and lymphoma is the most common associated malignancy. [2][3][4][5] It is hypothesized that EBV can interfere with normal lymphocyte signaling pathways leading to the aforementioned over-expression of Th1 cytokines, which can then trigger HLH. 7 The diagnosis of HLH is based on a combination of clinical and laboratory parameters as outlined in Table 1.…”
Section: Discussionmentioning
confidence: 99%